2007
DOI: 10.1038/sj.bjp.0707000
|View full text |Cite
|
Sign up to set email alerts
|

Increase in weight induced by muraglitazar, a dual PPARα/γ agonist, in db/db mice: adipogenesis/or oedema?

Abstract: Background and purpose: Muraglitazar, a dual PPARa/g agonist, caused a robust increase in body weight in db/db mice. The purpose of the study was to see if this increase in weight was due to oedema and/or adipogenesis. Experimental approach: The affinity of muraglitazar at PPARa/g receptors was characterized using transactivation assays. Preadipocyte differentiation, expression of genes for adipogenesis (aP2), fatty acid oxidation (ACO) and sodium reabsorption (ENaCg and Na þ , K þ -ATPase); haemodilution para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 25 publications
0
28
0
3
Order By: Relevance
“…Earlier studies using db/db mice showed that body weight increased significantly as the result of rosi treatment at a dosage of 10 mg kg À1 per day, 49,50 thereby indicating that rosi exerts an undesirable effect on body weight. According to the results of our in vivo study, evo evidenced an apparent antiobesity effect on body weight and the ratios of EWAT and liver weight/body weight in both cases of the absence and presence of rosi.…”
Section: Inhibitory Effect Of Evodiamine Ej Bak Et Almentioning
confidence: 99%
“…Earlier studies using db/db mice showed that body weight increased significantly as the result of rosi treatment at a dosage of 10 mg kg À1 per day, 49,50 thereby indicating that rosi exerts an undesirable effect on body weight. According to the results of our in vivo study, evo evidenced an apparent antiobesity effect on body weight and the ratios of EWAT and liver weight/body weight in both cases of the absence and presence of rosi.…”
Section: Inhibitory Effect Of Evodiamine Ej Bak Et Almentioning
confidence: 99%
“…One of the side effects of TZDs is tissue damage, which often results from fluid retention and edema (Hirsch et al, 1999;Tang et al, 2003;Mittra et al, 2007). Although some TZDs induce liver failure (Watkins and Whitcomb, 1998;Hirsch et al, 1999;Al-Salman et al, 2000), CG301360 slightly but substantially decreased the level of ALT and AST in db/db mice.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we demonstrate that this novel PPAR␣/␥ dual agonist effectively and selectively activates PPAR␣ and PPAR␥ and shows favorable effects on insulin sensitivity and lipid metabolism in db/db mice. Unlike many previous PPAR␣/␥ dual agonists (Hellmold et al, 2007;Mittra et al, 2007), CG301360 moderately activates PPAR␣ and PPAR␥. Furthermore, given that CG301360 action may not be primarily mediated through PPAR␦ propose that CG301360 might be free from PPAR␦-mediated side effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations